Improvement of protective oxide layers formed by high-frequency plasma electrolytic oxidation on Mg-RE alloy with LPSO-phase - Alisa O. Cheretaeva; Pavel A. Glukhov; Marat R. Shafeev; Alyona G. Denisova; Eugeny D. Borgardt; Anton V. Polunin; Alexander V. Katsman; Mikhail M. Krishtal (Chimica Techno Acta)
Oxide layers on Mg97Y2Zn1 magnesium alloy with strengthening LPSO-phase were formed by plasma electrolytic oxidation (PEO) in bipolar mode with frequency variation of forming current pulses (50 and 500 Hz) and addition of sodium aluminate or sodium silicate to alkali phosphate fluoride electrolyte. Microstructure, chemical and phase composition, corrosion and mechanical properties of the oxide layers formed were investigated. With increasing current frequency for both electrolytes, an increase in homogeneity of the oxide layers structure and a decrease in their porosity and fracturing at constant thickness were recorded. The oxide layers formed at 500 Hz even with some decrease in hardness have better adhesive strength and 2 orders of magnitude higher short-term corrosion resistance values. PEO of Mg-alloy with LPSO-phase in the electrolyte with addition of sodium aluminate in combination with increased pulse frequency (500 Hz) allows forming the best-quality uniform oxide layer with high hardness, adhesive strength and corrosion resistance properties. The use of electrolyte with addition of sodium silicate reduced the adhesive strength by 1.5 times and brought down the long-term corrosion resistance of oxide layers by an order of magnitude, as compared with the electrolyte with sodium aluminate. The reason for a significant improvement in the complex of protective properties of the oxide layers with an increase in the current pulse frequency is supposed to be a decrease in the power and duration of individual microarc discharges with simultaneous increase in their number per unit oxidized area.